2012
DOI: 10.1007/s11130-012-0291-3
|View full text |Cite
|
Sign up to set email alerts
|

Antigenotoxic Effects of Piquiá (Caryocar villosum) in Multiple Rat Organs

Abstract: This study investigated the in vivo genotoxicity of piquiá pulp (Caryocar villosum) and its potential antigenotoxicity on doxorubicin (DXR)-induced DNA damage by comet assay and micronucleus test. In addition, the phytochemicals present in piquiá pulp were determined. Piquiá fruit pulp (75, 150 or 300 mg/kg b.w.) was administered by gavage to Wistar rats for 14 days, and the animals received an injection of saline or DXR (15 mg/kg b.w., i.p.) 24 h before they were euthanized. The phytochemical analysis reveale… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
28
0
5

Year Published

2012
2012
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 27 publications
(33 citation statements)
references
References 27 publications
(33 reference statements)
0
28
0
5
Order By: Relevance
“…Gallic acid was described as the predominant compound among the phenolic compounds evaluated by Machado et al 34 in the aqueous extract of pequi pulp (from the region of Montes Claros, MG, Brazil). Almeida et al 35 identified gallic acid, by using HPLC-DAD-MS (high-performance liquid chromatography with diode array detection coupled to mass spectrometry), as the major phenolic compound observed in the lyophilized pequi pulp, corresponding to 31% of the total phenolics.…”
Section: Resultsmentioning
confidence: 99%
“…Gallic acid was described as the predominant compound among the phenolic compounds evaluated by Machado et al 34 in the aqueous extract of pequi pulp (from the region of Montes Claros, MG, Brazil). Almeida et al 35 identified gallic acid, by using HPLC-DAD-MS (high-performance liquid chromatography with diode array detection coupled to mass spectrometry), as the major phenolic compound observed in the lyophilized pequi pulp, corresponding to 31% of the total phenolics.…”
Section: Resultsmentioning
confidence: 99%
“…According to Almeida et al (2012), the occurrence of micronuclei, although it is not a carcinogenicity measurement, is often associated with the appearance of cancer, in view of the correlation between the increased frequency of micronucleated cells and detecting cancer in mammals. Table 1.…”
Section: Resultsmentioning
confidence: 99%
“…Cytotoxic and mutagenic activity of genotoxic agents almost always cause significant adverse effects, such as the development of tumors, after long exposure in the body (Almeida et al, 2012;Rothfuss et al, 2011). In this way, it becomes necessary quick, practical and efficient tests to early detect the toxic potential of these agents.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…With respect to the C. brasiliense almond, Lima et al (2007) showed a lower total carotenoid content (Lima et al, 2007); c (Almeida et al, 2012;; d (Almeida et al, 2012); e (Machado et al, 2013); f (Barreto et al, 2009); g (Torres et al, 2016b); h (Marx et al, 1997); * values found for almond oil; n.a. : not available; wb: wet basis; db: dry basis.…”
Section: Carotenoidsmentioning
confidence: 99%